Development of CSR through ethical leadership: Constructive role of ethical culture and intellectual capital - Irfan Ullah; Kashif ur Rehman; Raja Mazhar Hameed; Nida Zahid Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
In the contemporary era, the scandals of business leaders have shaken the trust and belief of stakeholders in corporate as well as in public sector organizations. The practitioners and scholars are progressively concerned about moral concerns associated with businesses, however, empirical and theoretical developments are still lacking. The prime purpose of the present study is to examine the relationship between ethical leadership and corporate social responsibility (CSR) by concentrating on the mediating role of the intellectual capital and ethical culture of the organization. Data for this study was collected through personally administered questionnaire survey from manufacturing sector of Pakistan and utilized 357 questionnaires for analysis. After the collection of data from respondents, statistical tools including correlation analysis and structural equation modeling were employed in the present study. This study concludes that ethical leadership positively affects CSR. This study finds the presence of ethical culture, social capital and human capital as mediator in relationship between ethical leadership and CSR. This study is the first attempt in Pakistan towards the perspective i.e. ethical leadership, ethical culture, and intellectual capital in relation to CSR.
Keywords: 330; ethical leadership; ethical culture; social capital; human capital; intellectual capital; corporate social responsibility (CSR)